KAJIAN PERTUMBUHAN LACTOBACILLUS CASEI PADA SUBSTRAT PORANG (AMORPHOPALLUS ONCOPHILLUS) - Farisa Sirtika Ramadhan; Hanifah Rahim; Dyah Hesti Wardhani (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Nowadays, probiotic products which can be found in market are milk and cereal based products. Porang or iles-iles (Amorphophallus onchophillus) is one of roots which grow commonly wildly in Indonesia. Porang contains high of glucomannan concentration, aproximatelly 41.137%. This research is aimed to study the ability of probiotic bacteria named Lactobacillus casei to grow in various concentration of porang flour( 0,5%w; 1%w and 5%w) and fermentations time and The effect of milk on the growth of probioticbacteria also studied. The results shows that pH of suspension decreased in the line with fermentation time, and porang concentration. And the addition of milk does not affect pH of the suspension. Bacteria concentration increased with the lenght of fermentation time and the high concentration of starch. Meanwhile, glucose level declined along with the lenght of fermentation time and the amount  of porang suspense. The increase of suspension density is proportional to the fermentation time and concentration of porang. The effect of milk supplement did not show any different in all cases.This research concluded that bacteria Lactobacillus casei could grow in porang suspense. In the future it’s needed to study the optimum condition for bacteria Lactobacillus casei grow in porang suspense.